Phosphonated polyimides: enhancement of proton conductivity at high temperatures and low humidity - Abouzari-Lotf, E. (Elsevier B.V., 2016)
A new class of highly conductive and durable polymer electrolyte membranes have been developed for fuel cell applications under elevated temperature and/or low relative humidity (RH). Highly phosphonated and fully aromatic diamine monomer was prepared via three-step high-yielding procedure from previously synthesized phosphonated bisphenol: halogen displacement of 1-fluoro-4-nitrobenzene, reducing of nitro groups, and hydrolysis of phosphonate ester groups. A series of phosphonated copolyimide ionomers with ion exchange capacity (IEC) of 2.4–4.6 mequiv g−1 were obtained by a typical polycondensation reaction followed by solution casting to form transparent and flexible membranes. Proton conductivity of the phosphonated membranes was comparable to that of the commercial perfluorinated ionomer at 100% RH. Typically, the conductivity value of up to 125 mS cm−1 was obtained for the membrane with IEC of 3.5 mequiv g−1 at 100 °C. However, by reducing the relative humidity the merits of phosphonated polyimides became more evidence and their dry state conductivity was 1–3 order of magnitudes higher than Nafion 115 and substantially higher than the values reported for phosphonated membranes. Thermogravimetric analysis and long-term proton conductivity study of phosphonated copolyimides at high temperatures (up to 160 °C) and low humidity confirmed small amount of undesired self-condensation of phosphonic acid groups compared with other phosphonated membranes.